Occurrence of ticks and tick-borne mixed parasitic microbiota in cross-bred cattle in District Lahore, Pakistan - Hasan,M. (2022)
Abstract The present study was focused on the incidence of ticks and tick-borne diseases (TTBD) in cross-bred cattle (Friesian x Sahiwal) of two farms (n = 2548) in district Lahore, Pakistan. We collected total of 572 ticks (adults and nymphs) and blood samples (10 ml) for microscopic i.e., blood smear test - Giemsa Stain (BST) and molecular analysis; Reverse Line Blot-General Primer-PCR (RLB-PCR) and Specie Specific Primer PCR (SP-PCR) from infested cattle (n = 100) from months of April to September. Results: The tick specie identified was Rhipicephalus microplus at both farms, with significant difference in infestations rate amongst both farms (p< 0.0001). The cross-bred cattle having higher ratio of Friesian blood and lower ratio of Sahiwal blood were mostly infested by ticks (p < 0.0458) and haemoparasites (p <0.474) and vice versa. The SP-PCR showed higher number of haemoparasites infection than BST, which revealed 16% T. annulata (p < 0.0001 and k value 0.485, 0.0001), 51% B. bigemina (p < 0.0001 and k value 0.485, 0.0001) and 15% A. marginale (p < 0.001 and k value 0.207, 0.001), respectively. The single infection with B. bigemina was 34% (n = 34/100) and A. marginale 6% (n = 6/100). The double infection with T. annulata/B. bigemina was 8% (n = 8/100) and B. bigemina/A. marginale 1% (n = 1/100). Whereas the triple infection with T. annulata/B. bigemina/A .marginale was 8% (n = 8/100). The phylogenetic study of isolated sequence of T. annulata revealed close homology to isolates from Iran (87%), B. bigemina to isolates from Cuba (94 to 100%) and A. marginale with isolates from Pakistan (99 to 98%).